EFFECTS OF DIETARY Diospyros mespiliformis LEAF AND STEM-BARK EXTRACTS ON GROWTH PERFORMANCE AND INTESTINAL MORPHOMETRICS IN Clarias gariepinus - MAGAJI, I.M.; ADENIYI, O.V. (Nigerian Journal of Fisheries, 2025)
The global criticism due to the deleterious effects of applying synthetic drugs in the production of food fish necessitates eco-friendly alternatives, like African ebony (AE). The AE have been reported to possess antimicrobial and antioxidant properties, but there is limited information on its application in aquaculture. Hence, this study investigated the phytochemical components and the effects of dietary supplementation with AE extracts on the growth performance and intestinal morphometrics of Clarias gariepinus. A preliminary phytochemical assessment was done, after which 240 fish fingerlings were randomly distributed into 12 tanks and fed with isonitrogenous and isocaloric basal diets containing 0.0, 0.5 leaf, 0.5 stem-bark, or 0.5 mL combined leaf and stem-bark ethanol extracts/100 g diet to apparent satiation for eight weeks. After the feeding trial, intestinal morphometrics were measured using standard procedures. Data obtained were analyzed using one-way analysis of variance at P< 0.05. Highest flavonoids and lower tannins were observed in AE ethanol extracts. Fish fed stembark extract exhibited significantly higher final weight, weight gain, specific growth rate, protein efficiency ratio, and lower feed conversion ratio, compared to other treatments. The fish fed diets supplemented with AE stem-bark also showed higher villi heights and width at the proximal and distal sections of the intestine, compared to other treatments. Therefore, 0.5 mLAE stem-bark/100 g diet is recommended for the production of C. gariepinus.